Comparative effects of vitamin D and methylprednisolone against ischemia/reperfusion injury of rabbit spinal cords - (:unkn) unknown (ELSEVIER, 2017)
Introduction: Recent studies have demonstrated the neuroprotective and immunomodulatory effects of 1,25-dihydroxyvitamin D3 (calcitriol), but no previous study has examined these effects on spinal cord ischemia/reperfusion (I/R) injury. Therefore, the present study aimed to evaluate whether calcitriol protects the spinal cord from I/R injury. Methods: Rabbits were randomized into four groups of eight animals: group 1 (laparotomy control), group 2 (ischemia control), group 3 (30 mg/kg intraperitoneal methylprednisolone at surgery), and group 4 (0.5 mu g/kg, intraperitoneal calcitriol for 7 days before I/R injury). The rabbits in the laparotomy control group underwent laparotomy only, whereas all rabbits in the other groups were subject to spinal cord ischemia by aortic occlusion for 20 min, just caudal to the renal artery. Malondialdehyde and catalase levels, myeloperoxidase and xanthine oxidase activities, and caspase-3 concentrations were analyzed. Finally, histopathological, ultrastructural, and neurological evaluations were performed. Results: After I/R injury, increases in malondialdehyde levels, myeloperoxidase and xanthine oxidase activities, and caspase-3 concentrations were found (p < 0.001 for all); by contrast, catalase levels decreased (p < 0.001). Calcitriol pretreatment was associated with lower malondialdehyde levels (p < 0.001), reduced myeloperoxidase (serum, p=0.018; tissue, p < 0.001) and xanthine oxidase (p < 0.001) activities, and caspase-3 concentrations (p < 0.001), but increased catalase levels (p < 0.001). Furthermore, calcitriol pretreatment was associated with better histopathological, ultrastructural, and neurological scores. Conclusion: Calcitriol pretreatment provided significant neuroprotective benefits following spinal cord I/R injury.
Keywords: Calcitriol; Ischemia/reperfusion injury; Methylprednisolone; Neuroprotection; Spinal cord injury; Vitamin D; ISCHEMIA-REPERFUSION INJURY; NEURONAL CELL-DEATH; QUALITY-OF-LIFE; 1,25-DIHYDROXYVITAMIN D-3; LIPID-PEROXIDATION; ISCHEMIC/REPERFUSION INJURY; XANTHINE-OXIDASE; FLUID DRAINAGE; D-RECEPTOR; D HORMONE